Corrigendum to "Removal of chromium(VI) from water and wastewater by using riverbed sand: Kinetic and equilibrium studies" [J. Hazard. Mater. 142 (2007) 449-454] (DOI:10.1016/j.jhazmat.2006.08.078) - Sharma Y.C.; Weng C.H. (My University, 2025)
[No abstract available]